The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/infdis/jiv231
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidisBacteremia Induces Brain Injury in Neonatal Mice via Toll-like Receptor 2-Dependent and -Independent Pathways

Abstract: Background. Staphylococcus epidermidis causes late-onset sepsis in preterm infants. Staphylococcus epidermidis activates host responses in part via Toll-like receptor 2 (TLR2). Epidemiologic studies link bacteremia and neonatal brain injury, but direct evidence is lacking.Methods. Wild-type and TLR2-deficient (TLR2−/−) mice were injected intravenously with S. epidermidis at postnatal day 1 prior to measuring plasma and brain cytokine and chemokine levels, bacterial clearance, brain caspase-3 activation, white/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 51 publications
7
36
1
Order By: Relevance
“…In addition, the strong proinflammatory TLR4 ligand, LPS, did not result in pleocytosis. Specific TLR2mediated effects may be of importance for neurologic outcome in the newborn, as we have previously shown that repeated stimulation of TLR2 results in impaired brain development [14] and that the gram-positive bacteria Staphylococcus epidermidis induces brain injury in neonatal mice, partly via TLR2-dependent pathways [27]. Furthermore, TLR2deficient mice are protected from neonatal hypoxia-ischemia, which further supports the importance of TLR2 in neonatal brain injury [13].…”
Section: Discussionsupporting
confidence: 57%
“…In addition, the strong proinflammatory TLR4 ligand, LPS, did not result in pleocytosis. Specific TLR2mediated effects may be of importance for neurologic outcome in the newborn, as we have previously shown that repeated stimulation of TLR2 results in impaired brain development [14] and that the gram-positive bacteria Staphylococcus epidermidis induces brain injury in neonatal mice, partly via TLR2-dependent pathways [27]. Furthermore, TLR2deficient mice are protected from neonatal hypoxia-ischemia, which further supports the importance of TLR2 in neonatal brain injury [13].…”
Section: Discussionsupporting
confidence: 57%
“…We have previously reported that S. epidermidis infection 14 h prior to HI in neonatal (PND4) mice sensitizes the brain to cerebral injury (14) and that intravenous injection of S. epidermidis at PND0 impairs brain development (26). S. epidermidis is known to activate TLR2 (27), but S. epidermidis induction of neonatal brain injury is both TLR2 dependent and independent (26). Furthermore, innate immune responses to S. epidermidis in preterm infants is known to be age-dependent (28).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal inflammation is driven in part by TLR signaling and can contribute to host defense against infection (27)(28)(29)(30). However, TLR-mediated cytokine induction can also contribute to pathology and disease, including inflammatory diseases of early life such as sepsis, BPD and perinatal brain injury (31)(32)(33). PTX, a nonspecific phosphodiesterase inhibitor that decreases transcription of proinflammatory cytokines, is a promising anti-inflammatory candidate for neonates.…”
Section: Discussionmentioning
confidence: 99%